A rare case study: pre-excited atrial fibrillation in Wolff-Parkinson white syndrome associated with partial ventricular septal defect - Snezhitskiy, Viktor; Matsiukevich, Marina; Direcksze, Naveen D. K. N.; Dineshkumar, Prithvi A.; Afham, M. N. M. (International Journal of Research in Medical Sciences, 2025)
Wolff–Parkinson–white (WPW) syndrome is a congenital disorder affecting the hearts’ conduction system, which is recognized by the existence of an accessory pathway (AP) that can lead to pre-excitation of ventricles, paroxysmal supraventricular tachycardias and in severe cases to sudden cardiac death. Thus, AP usually has non-decremental conduction allowing immediate ventricular activation which in case of AF leads to rapid ventricular response with high risk of transformation into ventricular fibrillation and cardiac arrest. Physical examination of this patient revealed the following clinical manifestations of WPW syndrome like severe tachycardia, dizziness and presyncope. The lab findings revealed an increase in the high-sensitive troponin I suggesting the underlying result from atrial fibrillation. And hyperbilirubinemia was shown in the biochemical analysis confirming the concomitant disease of this patient which is Gilbert’s Syndrome. The ECGs depicted the presence of a type A WPW pattern and paroxysmal form of atrial fibrillation (AF). The echocardiograms disclosed the presence of ventricular septal defect (VSD) in the membranous part of the interventricular septum. Both the ECGs and Echocardiograms revealed type A WPW pattern and paroxysmal form of atrial fibrillation respectively. The patient’s heart rate was monitored routinely in the intensive care unit with the help of 24-hour Holter monitoring device, breathing rate and blood pressure to detect the evaluation the patient’s prognosis. This article enhances the difficulties in differential diagnosis, experience of amiodarone uses in acute management, interventional treatment of pre-excited AF and VSD, because this can be a primary manifestation in young patients.